GAMBARAN KASUS HIV PADA IBU HAMIL DI DINAS KESEHATAN KOTA MEDAN - ENNI YUSRIANI (LP2MTBM MAKARIOZ, 2018)
Hummanodificiency syndrome is not a problem that is taken for granted the fact that it has threatened all levels of male and female society until December 200 reported 58 million people of the world are infected with HIV in that period 22 million people die or 7,000 people die of AIDS every day in Africa the number of sufferers HIV still increased in 2012 in Indonesia found 21,511 HIV cases and AIDS as many as 5,686 people this study aimed to find out the description of HIV cases in the Medan City Health Office.This type of research is descriptive, the population in this study were all HIV sufferers in the Medan City Health Office in 2016 as many as 19 people were taken in total sampling, the instrument used in the form of Distribution Tables and the data used was secondary data data analysis followed by discussing research results with existing theories and literature studies.From the results of this study it can be seen that the highest age picture of HIV cases is age 25-49 years as many as 19 cases (100%), the highest occupation in commercial sex workers as many as 5 cases (26.3%), the highest risk factor as many as PLWHA with HIV partners 19 cases (100%).Based on the results of the study it can be concluded that of the 19 cases of HIV based on age, most were found at the age of 25-49 years and based on occupation, the highest was PSK and based on the risk factors of most PLWHA with HIV partners. It is expected that health workers should make HIV and conduct surveillance to detect signs and symptoms of HIV in pregnant women